Management of alopecia in oncologic treatment patients - Turke, Karine Corcione; Fraga Neto, Jose Roberto; Oliveira, Deli Brito de; Pinto, Laissa Arruda; Schoueri, Jean; Salzano, Vanessa; Fabra, Dolores Gonzalez (ABCS Health Sciences, 2019)
Introduction: The treatment of cancer has been evolving every day. However, adverse effects such as dermatological changes have a great psychosocial impact on cancer patients. One dermatological change is alopecia, characterized by loss of eyebrow and scalp strands. Case report: Two cases of patients undergoing chemotherapy with partial and total alopecia were reported. Both were treated with Minoxidil, which was topically used, with complete repilation after three months. No adverse effects observed. Conclusion: Minoxidil topical lotion has proven to be an effective and safe method to treat partial and total alopecia in patients still undergoing cancer treatment.